Acute Lid Swelling: a Series of Unusual Cases, Treatment and Follow-up - Shojaati, G.; Chaloupka, K. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: There are many different aetiologies for acute lid swelling, including infection, inflammation, degeneration, tumours and trauma. We present five uncommon cases of acute lid swelling and give an overview of differential diagnoses for rapidly evolving eyelid swelling.History and Signs: We reviewed the charts of five patients with initial presentation of acute lid swelling. For the five patients, there were diagnoses of Churg Strauss syndrome, an allergic reaction to hyaluronic acid, lymphangioma, a ruptured dermoid cyst and a co-infected pre-existing orbital lesion that was only evident in the follow-up.Therapy and Outcome: Individual patients required totally different treatments. A ruptured dermoid is a dramatic problem that demands immediate surgical attention. Swelling in sinusitis in a child is just as important, but requires antibiotic treatment, careful follow-up and subsequent treatment of any secondarily infected pre-existing lesion. The less dramatic first presentations were more difficult to diagnose and required protracted observation and immunosuppressive treatment.Conclusions: The key to success often lies in the assessment of the patientʼs history and correctly timed surgery. Dramatic first manifestations were often easier to treat than initially low grade lid swelling. Unclear results, such as a low grade eosinophilia, should not be ignored.
Keywords: lid swelling; Churg-Strauss; plasmacytoma; lymphoma; dermoid; rhabdomyosarcoma; blepharochalasis; mucocele; IgG4; filler